A Hermeneutical Survey of the Book of Daniel: A Recipe for an Egalitarian Nigerian - Asuquo, O. O; Odey, E. A; Emeng, G. I.; Edet, F. F (Pharos Journal of Theology, 2023)
The fourth prophetic writing in the Old Testament, known as the Book of Daniel, has recently undergone an English translation. The primary focus of this text is centred on an individual by the name of Daniel. This individual is an ancient figure who is also mentioned in Ezekiel 14:14 and 28:3. Further examples of the aforementioned designation refer to a male progeny of David (1 Chronicle 3:1) and an individual belonging to the sacerdotal ancestry of Ithamar (Ezra 8; 2; Nehemiah 10:6). The afore-mentioned references provide substantiation that this particular terminology was widespread among the Jewish community in the period following the exile. Given the aforementioned, this paper examines the historical context of the individual known as Daniel, the authorship of the text, the discerned symbolic messages and their interpretation, criticism levelled against the book. The examination of the book through a hermeneutical lens is considered appropriate as a blueprint for the establishment of an egalitarian Nigerian society. The methodology adopted in this research is purely qualitative involving content analysis, critical evaluation of biblical text on the subject matter and a hermeneutical survey of scholastic views and analogy on the book of Daniel. The research objective was accomplished through a comprehensive utilisation of textual exegesis. Despite the criticisms levelled by certain scholars, the paper ultimately concludes that the book effectively justifies its relevance to the process of nation building.